High grade serous ovarian carcinomas originate in the fallopian tube. Issue 1 (December 2017) - Labidi-Galy, S. Intidhar; Papp, Eniko; Hallberg, Dorothy; Niknafs, Noushin; Adleff, Vilmos; Noe, Michael; Bhattacharya, Rohit; Novak, Marian; Jones, Siân; Phallen, Jillian; Hruban, Carolyn; Hirsch, Michelle; et al.
Abstract High-grade serous ovarian carcinoma (HGSOC) is the most frequent type of ovarian cancer and has a poor outcome. It has been proposed that fallopian tube cancers may be precursors of HGSOC but evolutionary evidence for this hypothesis has been limited. Here, we perform whole-exome sequence and copy number analyses of laser capture microdissected fallopian tube lesions (p53 signatures, serous tubal intraepithelial carcinomas (STICs), and fallopian tube carcinomas), ovarian cancers, and metastases from nine patients. The majority of tumor-specific alterations in ovarian cancers were present in STICs, including those affectingTP53, BRCA1, BRCA2 orPTEN . Evolutionary analyses reveal that p53 signatures and STICs are precursors of ovarian carcinoma and identify a window of 7 years between development of a STIC and initiation of ovarian carcinoma, with metastases following rapidly thereafter. Our results provide insights into the etiology of ovarian cancer and have implications for prevention, early detection and therapeutic intervention of this disease. It has previously been proposed that high-grade serous ovarian carcinoma (HGSOC) may originate from the fallopian tube. Here, the authors analyze genetic aberrances in fallopian tube lesions, ovarian cancers, and metastases from HGSOC patients and establish the evolutionary origins of HGSOC in the fallopian tube.